Heat transfer enhancement by helical screw tape coupled with rib turbulators - Nanan, Kwanchai; Pimsarn, Monsak; Thianpong, Chinaruk; Eiamsa-Ard, Smith (My University, 2014)
The influence of helical screw tape coupled with rib turbulators (HST-R) on thermohydraulic characteristics in a circular tube has been experimentally investigated. The experiments were performed under constant heat flux condition for Reynolds number between 6,000 and 20,000. The rib-pitch ratio (p/D) was varied from 1.0 to 3.0 while rib-height ratio (e/W) was varied from 0.5 to 1.5. The experimental results revealed that heat transfer and friction factor increase with increasing rib-height ratio (e/W) and decreasing rib-pitch ratio (p/D). For the range examined, the HST-Rs with moderate rib-pitch ratio (p/D = 2) and the largest rib-height ratio (e/W = 1.5) gave the maximum thermal performance factor while HST possessed thermal performance factor around average value of those of the tubes with HSTRs. The developed empirical correlations for Nusselt number, friction factor and thermal performance factor gave the predictions within ±4.4%, ±13% and ±4.2%, respectively as compared to the experimental data.
Keywords: Heat transfer exchanger; Helical tape; Rib turbulator; Swirl flow; Turbulence